2020
DOI: 10.3389/fphys.2020.560170
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Stimulates the Proliferation and Migration of Lymphatic Endothelial Cells Through Angiotensin Type 1 Receptors

Abstract: Background/Aim: The proliferation and migration of lymphatic endothelial cells (LECs) is essential for lymphatic vessel growth (also known as lymphangiogenesis), which plays a crucial role in regulating the tissue fluid balance and immune cell trafficking under physiological and pathological conditions. Several growth factors, such as VEGF-C, can stimulate lymphangiogenesis. However, the effects of angiotensin II (Ang II) on the proliferation and migration of mouse LECs and the underlying potential mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 30 publications
(55 reference statements)
1
17
0
Order By: Relevance
“…However, the present results indicated that LECs are the main cell type expressing VEGF‐C and VEGFR‐3. Although our recent data demonstrate that angiotensin II markedly increases VEGFR‐3 expression and lymphangiogenesis in mouse LECs though the angiotensin type I receptor, 30 the precise mechanisms by which pressure overload regulates VEGF‐C or VEGFR‐3 expression in LECs remain unclear. A previous study has shown that Tbx1, a member of the T‐box family of transcription factors, can upregulate VEGFR‐3 expression in endothelial cells by binding to an enhancer element within the Vegfr‐3 gene 31 .…”
Section: Discussionmentioning
confidence: 90%
“…However, the present results indicated that LECs are the main cell type expressing VEGF‐C and VEGFR‐3. Although our recent data demonstrate that angiotensin II markedly increases VEGFR‐3 expression and lymphangiogenesis in mouse LECs though the angiotensin type I receptor, 30 the precise mechanisms by which pressure overload regulates VEGF‐C or VEGFR‐3 expression in LECs remain unclear. A previous study has shown that Tbx1, a member of the T‐box family of transcription factors, can upregulate VEGFR‐3 expression in endothelial cells by binding to an enhancer element within the Vegfr‐3 gene 31 .…”
Section: Discussionmentioning
confidence: 90%
“…In addition, in contrast to SRC-IgG, neither AT-II nor ET-1 increased HMEC-1 proliferation. AT-II has, however, recently been associated with increased proliferation in lymphatic endothelial cells, and previously in human umbilical vein endothelial cells (HUVECs) [ 20 , 51 ]. AT 1 R stimulation triggered angiogenesis in both instances, a mechanism not involved in the present work.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we observed a positive effect of SIRT3 on VEGFC‐VEGFR3, where this growth factor is found includes myocardial cells, fibroblasts and macrophages, but the specific mechanism of action of SIRT3 upregulating VEGFC has yet to be elucidated. In addition, it was reported that low‐dose, short‐time administration of Ang II induced compensatory lymphangiogenesis in heart 34 . However, lymphangiogenic function was decreased in decompensatory stage of hypertensive cardiac remodelling with inflammation, fibrosis and heart failure 5 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was reported that low‐dose, short‐time administration of Ang II induced compensatory lymphangiogenesis in heart. 34 However, lymphangiogenic function was decreased in decompensatory stage of hypertensive cardiac remodelling with inflammation, fibrosis and heart failure. 5 Our study validated the latter.…”
Section: Discussionmentioning
confidence: 99%